If it's not what You are looking for type in the equation solver your own equation and let us solve it.
23=(x+3)+2x
We simplify the equation to the form, which is simple to understand
23=(x+3)+2x
Remove unnecessary parentheses
23=x+3+2x
We move all terms containing x to the left and all other terms to the right.
-1x-2x=+3-23
We simplify left and right side of the equation.
-3x=-20
We divide both sides of the equation by -3 to get x.
x=6.6666666666667
| x^4-5x^3+10x^2-80x-96=4i | | x^4-5x^3+10x^2-80x-96= | | 8(4x-4)= | | 9(4x+8)-6= | | 2x+3x=4x-4 | | (3+5)(2m-8)=0 | | 4x4y3/12x1y2 | | 6(12)+6n-70-4n=8 | | 22613.85=x+(x*.0825) | | 4x+9=-20 | | 23h-67=-44 | | (12x-6)+(16-5x)= | | 12x+3y+120=180 | | 7-4.5= | | 3(2r+6)=24 | | 9(2x+6)= | | 5d-c=12 | | 8(9x+9)+9(11-x)= | | (4x+1)+(11-4x)= | | 35+50x= | | (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 |